2014
DOI: 10.1007/s11010-014-2156-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of CD44(+) and CD44(−) gastric cancer cells

Abstract: CD44 is a cell surface protein and it is widely used as a cancer stem cell marker in various cancer types including gastric cancer. We conducted proteomic analysis in CD44(+) and CD44(-) gastric cancer cells to understand characteristics of CD44(+) and CD44(-) cells. In the present study, we sorted cells from the gastric cancer cell line MKN45 according to CD44 expression to separate out CD44(+) and CD44(-) cells. And we conducted RT-PCR to identify mRNA expression of cancer stem cell markers in CD44(+) and CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…For instance, global proteome profiling in pancreatic CSCs of xenograft mice tumours highlighted the involvement of signalling pathways related to apoptosis, cell proliferation, inflammation and metastasis in CSC regulation . Proteomic studies using cancer cell lines revealed the overexpression of Heat shock protein beta‐1 (HSPB1), Annexin A3 in breast CSCs and HSPA8, Ezrin, α‐enolase in gastric CSCs . However, there is paucity of data on differential proteomic analysis of primary hepatic CSCs.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, global proteome profiling in pancreatic CSCs of xenograft mice tumours highlighted the involvement of signalling pathways related to apoptosis, cell proliferation, inflammation and metastasis in CSC regulation . Proteomic studies using cancer cell lines revealed the overexpression of Heat shock protein beta‐1 (HSPB1), Annexin A3 in breast CSCs and HSPA8, Ezrin, α‐enolase in gastric CSCs . However, there is paucity of data on differential proteomic analysis of primary hepatic CSCs.…”
Section: Introductionsupporting
confidence: 92%
“…15 Proteomic studies using cancer cell lines revealed the overexpression of Heat shock protein beta-1 (HSPB1), Annexin A3 in breast CSCs 16 and HSPA8, Ezrin, α-enolase in gastric CSCs. 17 However, there is paucity of data on differential proteomic analysis of primary hepatic CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…All tumorspheres were maintained in culture for at least 14 days and passed three times to assure self-renewal ability. Stemness associated protein Sox-2 (SRY-box 2) [22] was also measured (Fig. 2a) to confirm sphere stem-like properties.…”
Section: Resultsmentioning
confidence: 99%
“…Besides introduced markers listed in Table 1 Apart from in vitro studies, analyzing clinical samples revealed that CD44 could be used in combination with clinicopathological information to improve the OSCC prognosis, since its overexpression, in tumor samples and peripheral blood of OSCC patients, was correlated to poor prognosis LGR5 [152,153] EpCAM [120] BMI1 [119,218] CD24 [122,125] OCT4 [118,119] SOX2 [118,119,[149][150][151] NANOG [118,119] Colon and rectum CD44 [166,[180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198]200] CD133 [161-165, 171-178, 186-188, 232] ABCG2 [75,158,159] ALDH1 [198,[222][223][224]…”
Section: Oral Cavitymentioning
confidence: 99%
“…For example, it has been reported that CD44 + GC cells were highly proliferative, invasive, therapy resistant, and tumorigenic [115][116][117], and expressed SC markers OCT4, SOX2, and NANOG [118,119]. In other studies, GC cells, with the main in vitro and in vivo properties of CSCs, were isolated from GC cell lines and patient tissues and characterized as CD44 + EpCAM + [120], CD44 + CD54 + [121], CD44 + CD24 + [122], CD44 + CD26 + [123], CD44 + ABCG2 + [124], and CD44 + CD24 + ALDH1 + [125] cells.…”
Section: Stomachmentioning
confidence: 99%